If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(k + -2) + -2k = -3 + 4 Reorder the terms: 3(-2 + k) + -2k = -3 + 4 (-2 * 3 + k * 3) + -2k = -3 + 4 (-6 + 3k) + -2k = -3 + 4 Combine like terms: 3k + -2k = 1k -6 + 1k = -3 + 4 Combine like terms: -3 + 4 = 1 -6 + 1k = 1 Solving -6 + 1k = 1 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 1k = 1 + 6 Combine like terms: -6 + 6 = 0 0 + 1k = 1 + 6 1k = 1 + 6 Combine like terms: 1 + 6 = 7 1k = 7 Divide each side by '1'. k = 7 Simplifying k = 7
| 8(8x-17)=312 | | 8(8x-17)=225 | | 5u+x=21 | | ln(4x-1)-ln(x^2+6)= | | 7(10x-2)=476 | | -1=-11+t | | 3x^2+7x+3=1 | | 23-3r=50 | | 3x(4+2y)-13x(-11+8y)= | | 5x^2-3x-12=-4 | | 5(8x-9)=355 | | b^2+3b-5=-7 | | 15y+7=62 | | 0.8x=2.7 | | 9m+2n-6m+10n= | | (5)/(2x-8) | | 26+7=36 | | logx=3.3 | | 2t+12=22 | | 8h-14=66 | | 9x^2+7x-5=3-7x | | 10(5x-7)=530 | | 10=x^3+7x^2+4x | | 6(8x+12)=504 | | r^2+7r+15=5 | | (7v-5)(v+3)=0 | | 5(9x-6)=285 | | 2(6x+4)=32 | | X^5+2x^4+8x^3+16x^2+7x+14=0 | | 32-4(8-6m)= | | log(2-x)(3x-x^2)=0 | | 5(3+4x)=95 |